Cardiovascular Disease - Cheung Angela; Fry Rick; Grace Sherry L; Stewart Donna E (BMC, 2004)
Abstract Health Issue Cardiovascular disease (CVD) is the leading cause of death in Canadian women and men. In general, women present with a wider range of symptoms, are more likely to delay seeking medial care and are less likely to be investigated and treated with evidence-based medications, angioplasty or coronary artery bypass graft than men. Key Findings In 1998, 78,964 Canadians died from CVD, almost half (39,197) were women. Acute myocardial infarction, which increases significantly after menopause, was the leading cause of death among women. Cardiovascular disease accounted for 21% of all hospital admissions for Canadian women over age 50 in 1999. Admissions to hospital for ischemic heart disease were more frequent for men, but the mean length of hospital stay was longer for women. Mean blood pressure increases with age in both men and women. After age 65, however, high blood pressure is more common among Canadian women. More than one-third of postmenopausal Canadian women have hypertension. Diabetes increases the mortality and morbidity associated with CVD in women more than it does in men. Depression also contributes to the incidence and recovery from CVD, particularly for women who experience twice the rate of depression as men. Data Gaps and Recommendations CVD needs to be recognized as a woman's health issue given Canadian mortality projections (particularly heart failure). Health professionals should be trained to screen, track, and address CVD risk factors among women, including hypertension, elevated lipid levels, smoking, physical inactivity, depression, diabetes and low socio-economic status.